Answer:
x > -6
Explanation:
Here in this question, we have to solve for x from the given inequality
-6 > -30- 4x.
We can solve the inequality equation by using the properties of inequality.
We have, -6 > -30 -4x
⇒ -6+30 > -4x
{The summation and subtraction rules of the inequality equation is similar to that of ordinary equations}
⇒24 > -4x
Dividing both sides by -1, we get,
⇒-24 < 4x
{In case of division of both the sides of an inequality by a negative number, the inequality sign changes from > to < and vice-versa}
⇒4x > -24
Dividing both the sides by 4, we get
⇒ x > -6 {There is same rule as equality equation for division both sides by a positive number} (Answer)